2017
DOI: 10.1002/sia.6205
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cigarette/e‐cigarette vapour on simulated pulmonary surfactant monolayers under physiologically relevant conditions

Abstract: The impact of cigarette/e-cigarette vapour on simulated pulmonary surfactant monolayers under physiologically relevant conditions http://researchonline.ljmu.ac.uk/5333/ Article LJMU has developed LJMU Research Online for users to access the research output of the University more effectively. Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Users may download and/or print one copy of any article(s) in LJMU Research Online to facilitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 40 publications
0
21
1
Order By: Relevance
“…Also in this case, it was impossible to estimate the real concentration of deposited vapor in the studied gas-liquid system. Contrary to the results of Przybyla et al (2017), Davies et al (2017) found a deflection and a shift of compression isotherm which suggested a direct interactions of EC-vapor components with the interfacial film of model LS. As a result, the surface tension could not be reduced to the same degree as if the EC-vapor components were absent.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Also in this case, it was impossible to estimate the real concentration of deposited vapor in the studied gas-liquid system. Contrary to the results of Przybyla et al (2017), Davies et al (2017) found a deflection and a shift of compression isotherm which suggested a direct interactions of EC-vapor components with the interfacial film of model LS. As a result, the surface tension could not be reduced to the same degree as if the EC-vapor components were absent.…”
Section: Discussioncontrasting
confidence: 99%
“…On the other hand, atomic force microscopy studies of the surfactant layer transferred to solid support revealed some alterations in lateral arrangement of surfactant components at the interface even at these low concentrations of EC-vapor components. Studies with the Langmuir trough were also published by Davies et al (2017) who used main LS lipids instead of animal-based surfactant. Lipid monolayer was directly exposed to vapor (aerosol), which was drawn into the experimental chamber.…”
Section: Discussionmentioning
confidence: 99%
“…Cannabis vapour and smoke contain the lipophilic Δ9‐THC molecule that is capable of disrupting a surfactant monolayer. This is so as these molecules can insert themselves directly into the monolayer, between surfactant molecules, and interrupt monolayer function, particularly in the solid phase during compression . This would result in a less rigid surface film with increased elasticity, which was noted herein.…”
Section: Resultsmentioning
confidence: 61%
“…Variation in the monomolecular structure results further to drug partitioning with either the drug causing expanded regions to become more condensed in nature via insertion within accessible areas or direct interaction between drug molecule and surfactant components, as modelled herein. Such modification to the surfactant film in the (deep) lung can influence structure‐function activity; however, in general terms, the surfactant film appears robust and resilient to external stressors (ie, drug substances and environmental toxins), and this allows it to fulfil its crucial biological function.…”
Section: Resultsmentioning
confidence: 99%